Assessment of Body Mass Index According Their Snacks Intake - Sathiyaseelan, V.; Nirosha, N.; Suthakaran, T.; Sulosana, P. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2018)
South Asian population suffer obesity associated complications at a lower Body Mass Index (BMI). There were only few published data on national level prevalence of obesity among Sri Lankan school students mainly from Jaffna district. Therefore, the aim of the present study was to determine the prevalence of overweight, underweight and the underlying socio-demographic correlates among A/L students of J/ Vadamarachchi Central Ladies' College (J/VCLC). It is a cross-sectional survey of 100 female students, aged 16 18 years, was chosen randomly from the J/VCLC during 2017. Students were asked to fill out a self-reported questionnaire that included questions on their eating, drinking habits. Also, their weight, height and body mass index were measured. Body mass index (BMI) was used to assess students' weight status. Standard procedures and equipments were used to measure the height and weight. BMI (Kg/m2) was calculated using height and weight. The study was conducted after obtained written consent from the school principal and the children themselves. When classified according to the BMI cut off values for Asians, 59% were normal weight, 34% were obese and 7% were underweight. Among them 71% were eating fast foods and only 19% were eating healthy snacks. In spite of the overall prevalence of overweight and obesity is increasing in the studied sample, results indicate that school students would possibly benefit from a nutrition and health promotion program to reduce the tendency of overweight and obesity, and to improve students' eating habits.
Keywords: Obesity; Body mass index; Food habits